Twist Functors and D-Branes - Burban, I. I.; Burban, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We discuss a categorical approach to the investigation of topological D-branes. Twist functors and their induced action on the cohomology ring of a manifold are studied. A nontrivial spherical object of the derived category of coherent sheaves of a reduced plane singular curve of degree 3 is constructed.